Modeling Radiation Doses for a Hypothetical Contaminated Site Using RESRAD-OFFSITE Code Faisalabad, Pakistan - Rafique, Q.; Hussain, M.; Wazir, Z.; Khan, F. (The Nucleus, 2017)
Naturally Occurring Radioactive Materials (NORMs) are one of the main sources of radiation exposure to humans and environment. To assess the impact of NORMs on human health and environment, different approaches (Deterministic & Probabilistic) are used globally. The radiological doses to the public from NORMs depend on the level of radioactivity, type of usage of the site, nature of the deposition and the location of the population with respect to the contaminated site. Different international organizations like International Commission on Radiological Protection (ICRP) and International Atomic Energy Agency (IAEA) have established international safety standards regarding protection from man-made and natural sources of ionizing radiations. In the current research work, the radiological doses to public, off-site, from the soil of a hypnotically contaminated area with radionuclides (40K, 137Cs, 226Ra and 232Th) at Nuclear Institute for Agriculture and Biology (NIAB), Faisalabad, Pakistan has been estimated using (RESRAD-OFF) code.The radiation doses due to different exposure pathways have also been estimated. The relation of different exposure pathways with the doses has also been analyzed